2010
DOI: 10.2965/jwet.2010.373
|View full text |Cite
|
Sign up to set email alerts
|

Screening of PHA-Producing Bacteria Using Biodiesel-Derived Waste Glycerol as a Sole Carbon Source

Abstract: Different sources of wastewater and soil were used to screen for PHA-producing bacteria using biodiesel-derived waste glycerol as a sole carbon source by the Nile red staining method together with polymer determination. Twelve out of twenty-six isolates from biodiesel-contaminated wastewater consortium were screened for their PHA accumulation ability by cultivation in mineral salt medium supplemented with waste glycerol. The AIK7 isolate was chosen as a potential PHA producer. The PHA production on waste glyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…A total of 120 isolates showed black-blue coloration when stained with Sudan black B, a preliminary screening agent for lipophilic compounds, and a total of 62 isolates showed positive result with Nile blue A staining, a specific dye for the presence of PHA granules. Teeka et al [29] used this method to screen the potential PHA-producing bacteria from soil, and Ramachandra and Abdullah [30] also observed the colonies formed on nutrient-rich medium under ultraviolet light (UV) to screen for the pink fluorescence which indicated the presence of PHA producers. Kitamura and Doi [31] first demonstrated this viable colony method on agar plates; they induced the isolates to accumulate PHA by culturing in E 2 medium, containing 2% (w/v) glucose before Nile blue A staining.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 120 isolates showed black-blue coloration when stained with Sudan black B, a preliminary screening agent for lipophilic compounds, and a total of 62 isolates showed positive result with Nile blue A staining, a specific dye for the presence of PHA granules. Teeka et al [29] used this method to screen the potential PHA-producing bacteria from soil, and Ramachandra and Abdullah [30] also observed the colonies formed on nutrient-rich medium under ultraviolet light (UV) to screen for the pink fluorescence which indicated the presence of PHA producers. Kitamura and Doi [31] first demonstrated this viable colony method on agar plates; they induced the isolates to accumulate PHA by culturing in E 2 medium, containing 2% (w/v) glucose before Nile blue A staining.…”
Section: Resultsmentioning
confidence: 99%
“…B. cepacia grown on crude glycerol generated by a small batch biodiesel processor at SUNY-ESF containing free fatty acids as a carbon source for comparable growth, yet much lower glycerol consumption, indicating that B. cepacia metabolized fatty acids, along with glycerol, for bacterial growth and PHA production. 88 Teeka et al 96 isolated a previously unidentified strain, AIK7, which also demonstrated enhanced bacterial growth, even improved PHA yield, when using waste glycerol containing free fatty acid instead of pure glycerol.…”
Section: Production and Characterization Of Polyhydrox-yalkanoates Frmentioning
confidence: 99%
“…The MSM supplemented with 2% (w/v) CG contained 1.44 g l -1 of total nitrogen, 1.28 g l -1 of total phosphorus, 27.5 g l -1 chemical oxygen demand (COD), and 1.384 g l -1 of sodium element [33]. It appeared that highest PHAs content of 45% cell dry weight (CDW) was achieved in 72 h ( Fig.…”
Section: Phas Biosynthesismentioning
confidence: 89%
“…Aerobic condition was maintained by shaking at 30°C and 150 rpm. PHAs and glycerol determination were described in Teeka et al [33].…”
Section: Batch Cultivationmentioning
confidence: 99%
See 1 more Smart Citation